DNA methylation - Bird, Adrian (Henry Stewart Talks, 2007)
DNA methylation as an epigenetic mark, location and patterns of methylated and nonmethylated CpG sites in the vertebrate genome, factors determining DNA methylation patterns, association of DNA methylation with stable gene silencing, e.g. methylation of CpG islands on the inactive X-chromosome, ensures long term repression of associated genes, recruitment of corepressors that impose a silent chromatin structure, repulsion of transcriptional activators by methyl-CpG leading to gene silencing, the link between human disorders, including cancer, Rett Syndrome and ICF syndrome, and defects in the DNA methylation system
Archived at 2016/06/22